Adaptation and dosimetric commissioning of a synchrotron-based proton beamline for FLASH experiments. (21st August 2022) - Yang, Ming; Wang, Xiaochun; Guan, Fada; Titt, Uwe; Iga, Kiminori; Jiang, Dadi; Takaoka, Takeshi; Tootake, Satoshi; Katayose, Tadashi; Umezawa, Masumi; Schüler, Emil; Frank, Steven; et al.
Abstract: Objective . Irradiation with ultra-high dose rates (>40 Gy s −1 ), also known as FLASH irradiation, has the potential to shift the paradigm of radiation therapy because of its reduced toxicity to normal tissues compared to that of conventional irradiations. The goal of this study was to (1) achieve FLASH irradiation conditions suitable for pre-clinical i n vitro and in vivo biology experiments using our synchrotron-based proton beamline and (2) commission the FLASH irradiation conditions achieved. Approach . To achieve these suitable FLASH conditions, we made a series of adaptations to our proton beamline, including modifying the spill length and size of accelerating cycles, repurposing the reference monitor for dose control, and expanding the field size with a custom double-scattering system. We performed the dosimetric commissioning with measurements using an Advanced Markus chamber and EBT-XD films as well as with Monte Carlo simulations. Main results . Through adaptations, we have successfully achieved FLASH irradiation conditions, with an average dose rate of up to 375 Gy s −1 . The Advanced Markus chamber was shown to be appropriate for absolute dose calibration under our FLASH conditions with a recombination factor ranging from 1.002 to 1.006 because of the continuous nature of our synchrotron-based proton delivery within a spill. Additionally, the absolute dose measured using the Advanced Markus chamber and EBT-XD films agreed well, with average and maximum differences of 0.32% and 1.63%, respectively. We also performed a comprehensive temporal analysis for FLASH spills produced by our system, which helped us identify a unique relationship between the average dose rate and the dose in our FLASH irradiation. Significance. We have established a synchrotron-based proton FLASH irradiation platform with accurate and precise dosimetry that is suitable for pre-clinical biology experiments. The unique time structure of the FLASH irradiation produced by our synchrotron-based system may shed new light onto the mechanism behind the FLASH effect.